Math, asked by rabiprasad1220p63nb7, 1 year ago

plzz solve both for exam ok

Attachments:

Answers

Answered by jhane1
0


Check it in NCERT
u will definitely get your answer
Answered by sivaprasath
0
1/

Solution:

_____________________________________________________________

Given:

3a + 2b = 5c,.

&

abc = 0
_____________________________________________________________

To Find :

Value of 27a³ + 8b³ - 125c³

_____________________________________________________________

27a³ + 8b³ - 125c³

=>  (3a)³ + (2b)³ + (-5c)³

we know that,

a³ + b³ + c³ - 3abc = (a + b + c)(a² + b² + c² -ab -bc -ac)

=> (3a)³ + (2b)³ + (-5c)³ - 3(0) = (3a + 2b - 5c)((3a)² + (2b)² +(-5c)² -(3a)(2b) -(2b)(-5c) - (3a)(-5c))

=> (3a)³ + (2b)³ + (-5c)³ = (0)(9a² + 4b² + 25c² -6ab +10bc +15ac)

=> 27a³ + 8b³ -125c³ = 0

_____________________________________________________________

2/

Solution:

_____________________________________________________________

Given:

x^2 +  \frac{1}{x^2} = 66

_____________________________________________________________

To Find :

The value of x^3 -  \frac{1}{x^3}

_____________________________________________________________

We know that,

(a + b)² = a² + 2ab + b²,.

(a+ b)² - 2ab = a² + b²,..

so,

(x)^2 + ( \frac{1}{x})^2 = 66 ... (i)

Adding 2 both the sides,

=> x^2 +  \frac{1}{x^2}  + 2 = 66 + 2

=> x^2 +  \frac{1}{x^2} + 2(x)( \frac{1}{x^2} ) = 68

=> (x +  \frac{1}{x} )^2 = 68...(ii)

=>  x +  \frac{1}{x} =  \sqrt{68}

=>  \frac{x^2 + 1}{x}  =  \sqrt{68}

=> x^2 + 1 =   \sqrt{68}  x

=> x^2 -  \sqrt{68} x +  1 = 0

=> [tex] x^{2} - \sqrt{68}x = -1 [/tex]]

=> x^2 - 2( \frac{ \sqrt{68}x}{2}) = -1 (multiplying and dividing by 2)

=> x^2 - 2( \frac{ \sqrt{68}x}{2}) + (\frac{ \sqrt{68}}{2})^2 = -1+ (\frac{ \sqrt{68}}{2})^2 (Adding √68/2 both the sides)

=> (x -  \frac{ \sqrt{68}}{2})^2 = -1 +  \frac{68}{4}

=> (x -  \frac{ \sqrt{17(4)}}{2})^2 =  \frac{-4+68}{4}

=> (x -  \frac{ 2\sqrt{17}}{2})^2 =  \frac{64}{4}

=> (x - \sqrt{17} )^2 = 16

=> x -  \sqrt{17} = 4

=> x = 4 +  \sqrt{17}

And we know that,

a³ - b³ = (a-b)(a² + ab + b²),.

=> x^3 - \frac{1}{x^3} = (x -  \frac{1}{x})(x^2 - (x)( \frac{1}{x})+ ( \frac{1}{x^2}))

=> (4+ \sqrt{17} -  \frac{1}{4 +  \sqrt{17}})(66 + 1)

=> (4+ \sqrt{17} -  \frac{4- \sqrt{17}}{16-17})(67)

=> (4+ \sqrt{17} + 4 - \sqrt{17})(67)

=> (8)(67)

=> 536

_____________________________________________________________

                                     Hope it Helps!!

sivaprasath: Mark as Brainliest,.
sivaprasath: plz
Similar questions